The Influence of Good Corporate Governance on Sustainability Reporting: The Moderating Role of Leverage - Nurdina nurdina; Rovila El Maghviroh (Jurnal Penelitian Ekonomi dan Akuntansi JPENSI, 2025)
This study aims to analyze the effect of Good Corporate Governance (GCG) mechanisms (independent commissioners, audit committees, and managerial ownership) on the quality of sustainability reports in mining companies listed on the Indonesia Stock Exchange for the period 2021–2023, as well as to examine the role of the Debt to Equity Ratio (DER) as a moderating variable. The research employed a quantitative approach with purposive sampling techniques, resulting in a sample of 29 companies. Data were obtained from annual reports and GRI-based sustainability reports. The analysis was conducted through multiple regression and moderated regression analysis (MRA). The results indicate that the audit committee has a positive and significant impact on sustainability reports, whereas independent commissioners and managerial ownership have no effect. DER is not proven to moderate the relationship between GCG mechanisms and the quality of sustainability disclosure. These findings confirm that the effectiveness of internal oversight through the audit committee is more decisive than ownership structure or external pressure from the funding structure. This study contributes theoretically to the strengthening of stakeholder theory and legitimacy theory, and provides practical implications for regulators and management to enhance the quality of sustainable governance in the mining sector.